La riscoperta dell’idealismo filosofico di Benedetto Croce tramite la traduzione del saggio “Perché non possiamo non dirci «cristiani»” - Muszyńska, Katarzyna (Translatoryka i Translacje. Przekład w XXI wieku. Wyzwania – możliwości – trendy, 2020)
The present analysis focuses on the modern methodology of translating several philosophical treatises by a famous Italian thinker of the 20th century, Benedetto Croce, into Polish. The author of the article presented the self-translation of selected extracts of the well-known essay Perché non possiamo non dirci «cristiani» released in 1942. The philosopher affirms in this text that Christianity was the biggest revolution of the soul in the human history and that is why we cannot reject its impact on the individuals, on the politics and on the morality. The poetic and cultural allusions and the archaism of the language made the essay an interesting example of a philosophical work which at the same time can preserve its universalism and become a reflection of the linguistic and cultural transformations of the 20th century.